The Amphibious Mudskipper: A Unique Model Bridging the Gap of Central Actions of Osmoregulatory Hormones Between Terrestrial and Aquatic Vertebrates - Katayama, Yukitoshi; Sakamoto, Tatsuya; Takanami, Keiko; Takei, Yoshio (Frontiers in Physiology, 2018)
Body fluid regulation, or osmoregulation, continues to be a major topic in comparative physiology, and teleost fishes have been the subject of intensive research. Great progress has been made in understanding the osmoregulatory mechanisms including drinking behavior in teleosts and mammals. Mudskipper gobies can bridge the gap from aquatic to terrestrial habitats by their amphibious behavior, but the studies are yet emerging. In this review, we introduce this unique teleost as a model to study osmoregulatory behaviors, particularly amphibious behaviors regulated by the central action of hormones. Regarding drinking behavior of mammals, a thirst sensation is aroused by angiotensin II through direct actions on the forebrain circumventricular structures, which predominantly motivates them to search for water and take it into the mouth for drinking. By contrast, aquatic teleosts can drink water that is constantly present in their mouth only by reflex swallowing, and angiotensin II induces swallowing by acting on the hindbrain circumventricular organ without inducing thirst. In mudskippers, however, through the loss of buccal water by swallowing, which appears to induce buccal drying on land, angiotensin II motivates these fishes to move to water for drinking. Thus, mudskippers revealed a unique thirst regulation by sensory detection in the buccal cavity. In addition, the neurohypophysial hormones, isotocin and vasotocin, promote migration to water via isotocin receptors in mudskippers. Vasotocin is also dipsogenic and the neurons in the forebrain may mediate their thirst. Vasotocin regulates social behaviors as well as osmoregulation. The vasotocin-induced migration appears to be a submissive response of subordinate mudskippers to escape from competitive and dehydrating land. Together with implications of vasotocin in aggression, mudskippers may bridge the multiple functions of neurohypophysial hormones. Interestingly, cortisol, an important hormone for seawater adaptation and stress response in teleosts, also stimulates the migration toward water, mediated possibly via the mineralocorticoid receptor. The corticosteroid system that is responsive to external stressors can accelerate emergence of migration to alternative habitats. In this review, we suggest this unique teleost as an important model to deepen insights into the behavioral roles of these hormones in relation to osmoregulation.